(untitled) (Iranian Journal of Kidney Diseases, 2021)
Coronavirus disease 2019 (COVID‑19) was identified in December 2019 and is still expanding in most parts of the world. The wide variety of affected organs is likely based upon the shared expression of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) important entry-receptor angiotensin-converting enzyme 2 (ACE2). For this reason, the broad distribution of ACE2 receptors in different tissues plays a crucial role in the multi-organ dysfunction and fatality due to COVID-19. Because of the high prevalence of acute kidney injury (AKI) in patients with COVID-19, we review the molecular understanding into viral infection mechanisms and implications for AKI. Furthermore, mechanisms of the AKI to chronic kidney disease (CKD) progression, such as the relative contribution of immune cell reaction, fibroblasts activation, endothelial dysfunction, and subsequent hypoxia may contribute to the association of AKI with worse outcomes during this virus pandemic. We highlight the state of the knowledge on SARS-CoV-2-dependent mechanisms for AKI and list the potential management choices for the prevention of AKI aggravation and the impending possibility of CKD. Finally, we intend to provide a much better understanding of why Coronavirus induces AKI and its subsequent progression to CKD in the coming years and further discuss the acute and long-term renal consequences. DOI: 10.52547/ijkd.6311